'An aid to loveliness': lavender, femininity and the affective economy of English beauty. (January 2023) - Lorimer, Hayden
Abstract: By considering the cultural production, placement, promotion and personalization of a fragrant aromatic, this article attempts to compile a historical geography of lavender and loveliness. The purpose of this experimental exercise is threefold. First, to examine the emergence of modern affective economies based around fashioning the self, directed at women's physical appearance and delineating desirable new standards of femininity. Second, to interrogate how the mid twentieth century beauty industry formulated the new concept of facial skincare in which ideas of a healthy complexion was complexly encoded with an aesthetic of whiteness. Third, to understand how the exercise of researching and writing such a sensory history is a means to address the challenges which non-representational theory has raised for scholarship in historical geography. Empirically, the article focuses on the operations of the House of Yardley, one of London's oldest perfumeries and beauty companies, and its foremost perfumier-cosmetician of the modern era, W.A. Poucher. To explore how the scent of lavender was deployed in markets globally, promoting a selectively English version of loveliness, it travels to various points along the supply line between the fragrant flower and female face. Highlights: Sensory histories of fragrances and aromatics are a new form of study. Coupling lavender and loveliness is an experiment in historical geography. The House of Yardley was a key agent in defining English beauty. Feminine beauty standards configured cultural ideas about whiteness. W.A. Poucher was a key cultural figure in the global beauty industry.